2012
DOI: 10.1007/s10620-012-2482-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-Expanding Metal Stents (SEMS) for Preoperative Biliary Decompression in Patients with Resectable and Borderline-Resectable Pancreatic Cancer: Outcomes in 241 Patients

Abstract: SEMS should be considered for patients with obstructive jaundice and resectable or borderline resectable pancreatic cancer, especially if surgery is not planned immediately as a result of preoperative chemoradiation. These stents appear to be safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…There have been some reports regarding late complications of biliary SEMS placement such as bile duct perforation due to mechanical pressure by a SEMS and hepatic abscess due to 3 stent occlusion. [1][2][3] This is the first report of an extrahepatic abscess at the eccentric site as a late complication of SEMS placement. The eccentric abscess can result from a combination of SEMS placement and neoadjuvant chemoradiation that will contribute to tissue damage and delayed healing at the bile duct.…”
mentioning
confidence: 79%
“…There have been some reports regarding late complications of biliary SEMS placement such as bile duct perforation due to mechanical pressure by a SEMS and hepatic abscess due to 3 stent occlusion. [1][2][3] This is the first report of an extrahepatic abscess at the eccentric site as a late complication of SEMS placement. The eccentric abscess can result from a combination of SEMS placement and neoadjuvant chemoradiation that will contribute to tissue damage and delayed healing at the bile duct.…”
mentioning
confidence: 79%
“…Mean time between stent placement and surgery to relieve hyperbilirubinemia and provide patients with an optimal nutritional status was 4 weeks (3,26). With a retrospective design and lacking a control group, Singal et al demonstrated that placing a metallic stent added no technical difficulties during surgery, and was a safe and effective measure in the setting of resectable or potentially resectable neoplastic lesions following cancer therapy (3,27).…”
Section: Preoperative Drainage Preliminary Studiesmentioning
confidence: 99%
“…35,36 SEMS have also been shown to be better than plastic stents for palliative stenting as well. A Cochrane database review evaluated nine studies that compared the stent materials.…”
Section: Q3mentioning
confidence: 99%